SEQUEL: Prevalence of dental caries in Saudi Arabia: A systematic review and Meta-analysis - Soban Qadir Khan; Haneen A. Alzayer; Shahad T. Alameer; Muhammad Ajmal Khan; Nazeer Khan; Haitham AlQuorain; Mohammed M. Gad (Saudi Dental Journal)
This meta-analysis investigated the prevalence of dental caries throughout the Kingdom of Saudi Arabia (KSA) between 2011 and 2023 as a follow-up to a previously published review in 2013 by Khan et al. and aimed to provide an update on the current status of caries prevalence in the KSA. A literature search was conducted, and thirty-three articles were included in the final analysis. To determine the prevalence of caries in primary teeth, the 2- to 12-year-old Saudi population was included in the search, and an age range of 6–18 years was used for permanent teeth. The prevalence of caries in the primary and permanent dentition was analyzed separately. As the included studies for the primary and permanent teeth had insignificant heterogeneity, fixed-effect models and forest plots were used to evaluate caries prevalence in both dentitions. In the primary dentition, the mean decayed-missing-filled teeth (dmft) index was 4.14 (95 % confidence interval (CI): 3.11–5.18), with an average prevalence of 75.43 %. For the permanent teeth, the mean DMFT (uppercase used for permanent dentition) was 1.28 (95 % CI: 0.93–1.64), with an average prevalence of 67.7 %. The average dmft/DMFT scores decreased in both primary and permanent teeth compared to the previous meta-analysis by Khan et al., suggesting a beneficial effect of preventative measures on caries prevalence. Continuing these measures is necessary to maintain the downward trend of caries prevalence in the KSA.